Role of the University in the social mobility of the Saudi woman: A case of Prince Sattam University - Sharabi, Wadad Abdullah (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the role of Prince Sattam University as a model in the development of the social mobility of Saudi women and to reveal the effect of some variables (the scientific specialization of the residence class) for the role of Prince Sattam University as a model in the social mobility of female students. (48) divided into four main dimensions of social mobility, and was selected a random sample consisting of (200) students from the University of Prince Sattam. The study found that the University of Prince Sattam as a role model in achieving social mobility with a mean average of 4.30, a standard deviation of 0.98, a verbal assessment (strongly agree), economic mobility with an average of 4.43, a standard deviation of 0.89, ), Cultural mobility at an average of 3.75, a standard deviation of 0.83, a verbal estimate of (I agree), political mobility at an average of 3.93, a standard deviation of 0.90, a verbal assessment of students The study showed that there is no difference in the responses of female students due to the variable (specialization of the academic class in residence) in all the social mobility. The study also presented a model from the point of view of the students to activate the role of the university in helping students develop their social mobility. The role of the university in developing the social mobility of its students, and urging students to participate in political, cultural, economic and social, and the importance of the role of the university in introducing students to the importance of social mobility